Phase I open label liver-directed gene therapy clinical trial for acute intermittent porphyria - D'Avola, Delia; Gil-Fariña, Irene; Schmidt, Manfred (Journal of hepatology, 2016)
Acute intermittent porphyria (AIP) results from porphobilinogen deaminase (PBGD) haploinsufficiency, which leads to hepatic over-production of the neurotoxic heme precursors porphobilinogen (PBG) and delta-aminolevulinic acid (ALA) and the occurrence of neurovisceral attacks. Severe AIP is a devastating disease that can only be corrected by liver transplantation. Gene therapy represents a promising curative option. The objective of this study was to investigate the safety of a recombinant adeno-associated vector expressing PBGD (rAAV2/5-PBGD) administered for the first time in humans for the treatment of AIP. In this phase I, open label, dose-escalation, multicenter clinical trial, four cohorts of 2 patients each received a single intravenous injection of the vector ranging from 5×1011 to 1.8×1013 genome copies/kg. Adverse events and changes in urinary PBG and ALA and in the clinical course of the disease were periodically evaluated prior and after treatment. Viral shedding, immune response against the vector and vector persistence in the liver were investigated. Treatment was safe in all cases. All patients developed anti-AAV5 neutralizing antibodies but no cellular responses against AAV5 or PBGD were observed. There was a trend towards a reduction of hospitalizations and heme treatments, although ALA and PBG levels remained unchanged. Vector genomes and transgene expression could be detected in the liver one year after therapy. rAAV2/5-PBGD administration is safe but AIP metabolic correction was not achieved at the doses tested in this trial. Notwithstanding, the treatment had a positive impact in clinical outcomes in most patients. Studies in an acute intermittent porphyria (AIP) animal model have shown that gene delivery of PBGD to hepatocytes using an adeno-associated virus vector (rAAV2/5-PBG) prevent mice from suffering porphyria acute attacks. In this phase I, open label, dose-escalation, multicenter clinical trial we show that the administration of rAAV2/5-PBGD to patients with severe AIP is safe but metabolic correction was not achieved at the doses tested; the treatment, however, had a positive but heterogeneous impact on clinical outcomes among treated patients and 2 out of 8 patients have stopped hematin treatment. The observational phase was registered at Clinicaltrial.gov as NCT 02076763. The interventional phase study was registered at EudraCT as n° 2011-005590-23 and at Clinicaltrial.gov as NCT02082860.